Increasing Denture Retention using Compound Denture Technique – A Case Report - Wirayudha, Agam; Kamadjaja, Michael Josef Kridanto; Agustono, Bambang (Indonesian Journal of Dental Medicine, 2018)
Background: Treating missing tooth with denture, in some cases, still leave the patient unfulfilled. Good mastication and retention are the main considerations especially for those who require more retentions. In some cases, combination of partial and fixed denture the best approach to achieve better functional and retention results. Purpose: To report compound denture procedures with good mastication and retention as the main considerations. Case: A 43-year-old male patient reported a complaint of chewing difficulty due to missing right upper front teeth caused by work accident and extracted posterior. Patient wanted to wear partial denture to regain good mastication. Case management: Compound denture was chosen to optimize the remaining teeth for better functional and aesthetic. Zirconia all ceramic fixed dentures were fabricated on 13, 14, 15 with an occlusal rest on 13 and 15. Pontic on the 14 used ridge lap design. Discussion: Compound denture is a combination of removable and fixed denture where a minor connector of a removable denture should involve a fixed denture. Fixed denture shall be fabricated first and then removable denture. Conclusion: The definitive restoration of this case was compound denture, which is a combination of partial denture metal frame and fixed denture to restore the good mastication and retention.